2018
DOI: 10.21037/jtd.2018.08.64
|View full text |Cite
|
Sign up to set email alerts
|

Micropapillary or solid pattern predicts recurrence free survival benefit from adjuvant chemotherapy in patients with stage IB lung adenocarcinoma

Abstract: Background: Our study aimed to evaluate the prognostic significance and adjuvant chemotherapy (ACT) benefits of a micropapillary/solid (MS) pattern in patients with stage IB lung adenocarcinoma.Methods: Patients with pathologically-confirmed stage IB adenocarcinoma who underwent surgical resection between January 2009 and December 2011 were included. The tumors were reclassified into three categories: MS patterns absent (MS−); non-predominant MS patterns (MS+); predominant MS (MS++). The correlations of progno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 33 publications
0
24
1
Order By: Relevance
“…This highlights that those with poorly differentiated adenocarcinoma might fare worse than the other groups with systemic chemotherapy, which is similar to previous research showing that major solid patterns indicate inferior OS after systemic treatment [ 9 ]. Nevertheless, this result seems to conflict with other studies’ conclusions [ 36 , 37 , 38 , 39 ]. It is possible that different regimens may influence survival, especially as the method of chemotherapy can vary over time [ 29 ].…”
Section: Discussioncontrasting
confidence: 86%
“…This highlights that those with poorly differentiated adenocarcinoma might fare worse than the other groups with systemic chemotherapy, which is similar to previous research showing that major solid patterns indicate inferior OS after systemic treatment [ 9 ]. Nevertheless, this result seems to conflict with other studies’ conclusions [ 36 , 37 , 38 , 39 ]. It is possible that different regimens may influence survival, especially as the method of chemotherapy can vary over time [ 29 ].…”
Section: Discussioncontrasting
confidence: 86%
“…And, patients who had undergone wedge resection and those who had an unknown lymph node status (Nx) were also excluded as they limited accurate stage evaluation. Since a micropapillary pattern is a pathological predictor of recurrence, it was considered a high-risk factor in this study [8][9][10]. Furthermore, previous studies have shown that lymphatic invasion is associated with recurrence [11,12].…”
Section: Study Design and Participantsmentioning
confidence: 91%
“…Patients were excluded from the study cohort if one of the following criteria was met: (1) receipt of induction therapy; (2) presence of multiple primary lung cancers; (3) receipt of targeted therapy or immunotherapy; (4) lack of information on lymph nodes status. Platinum-based ACT (cisplatin plus docetaxel or pemetrexed) was performed in patients with high-risk factors including poor differentiated tumor, visceral pleural invasion, vascular invasion, and SR. 8 Age, performance status, and patients’ preference were also considered. No mortality related to chemotherapy was detected among patients who underwent four cycles of ACT.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Hitherto, several studies have reported potential survival advantages of ACT in stage IB patients with high-grade (micropapillary/solid-predominant) ADC. 7 , 8 In recent years, tumor spread through air spaces (STAS), has been recognized as a novel invasion pattern in stage I ADCs, which was associated with poor recurrence-free and overall survival. 9 11 Increasing evidence has revealed a potential relationship between resection types and patient survival in STAS-positive ADC.…”
Section: Introductionmentioning
confidence: 99%